2002
DOI: 10.1038/sj.onc.1205146
|View full text |Cite
|
Sign up to set email alerts
|

Centrosome abnormalities, recurring deletions of chromosome 4, and genomic amplification of HER2/neu define mouse mammary gland adenocarcinomas induced by mutant HER2/neu

Abstract: The conditional expression of activated HER2/neu gene under its endogenous promoter in the mammary epithelium of the mouse results in accelerated lobular development and focal mammary tumors. Carcinogenesis, however, requires ampli®cation and considerably increased expression levels of oncogenic neu. Deducing from the multiple genetic aberrations required for human breast cancer to develop, we hypothesized that in addition to the over-expression of an activated HER2/ neu, secondary aberrations would occur. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
82
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(89 citation statements)
references
References 32 publications
(32 reference statements)
7
82
0
Order By: Relevance
“…By CGH we observed an ANCA of 8.1 for the Brca1-deficient mammary tumors. This number is higher than in murine tumors induced by overexpression of an oncogene, such as in MMTV-c-myc (ANCA=5.5) or Erbb2 (ANCA-2.7) transgenics Montagna et al, 2002). Conditional knockout of the Brca1 tumor suppressor gene may more closely model familial breast cancer as the second allele is only mutated as the mice reach maturity (Xu et al, 1999a).…”
Section: Discussionmentioning
confidence: 97%
“…By CGH we observed an ANCA of 8.1 for the Brca1-deficient mammary tumors. This number is higher than in murine tumors induced by overexpression of an oncogene, such as in MMTV-c-myc (ANCA=5.5) or Erbb2 (ANCA-2.7) transgenics Montagna et al, 2002). Conditional knockout of the Brca1 tumor suppressor gene may more closely model familial breast cancer as the second allele is only mutated as the mice reach maturity (Xu et al, 1999a).…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies with the ErbB2 KI model indicated that one important genomic alteration involved in tumor progression is the loss of a chromosomal region spanning the 14-3-3σ locus that is correlated with loss of 14-3-3σ expression (15,17). To directly address whether loss of 14-3-3σ is a critical event in ErbB2-driven tumor progression, we intercrossed mice bearing the conditional 14-3-3σ allele to ErbB2 KI mice to generate cohorts of ErbB2 KI female mice with one or two conditional 14-3-3σ alleles.…”
Section: Loss Of 14-3-3s Results In Both Accelerated Erbb2 Mammary Tumentioning
confidence: 99%
“…S1C). Given that the average tumor chromosome 4 (15). Refined CGH/BAC analyses revealed that in addition to the erbB2 amplicon, there was a frequent loss of a chromosomal region spanning the 14-3-3σ tumor suppressor locus (16,17).…”
Section: Loss Of 14-3-3s Results In Both Accelerated Erbb2 Mammary Tumentioning
confidence: 99%
“…Tumor progression in these strains is associated with a dramatic elevation in the levels of both ErbB2 mRNA and protein. Remarkably, the elevated expression of ErbB2 also correlates with selective genomic amplification of the activated ErbB2 allele (Andrechek et al 2000;Montagna et al 2002;Hodgson et al 2005). Thus, as in human breast cancers, amplification of ErbB2 appears to be a critical event in mammary tumor progression in this mouse model.…”
Section: Transgenic Models Of Erbb2-induced Tumor Progressionmentioning
confidence: 88%
“…Tumorigenesis in the ErbB2 KI model is also associated with a number of other alterations, including centrosome abnormalities and recurrent deletions of chromosome 4 (Montagna et al 2002). Further refined mapping of chromosome 4 region has revealed that these tumors have frequently loss of expression of the tumor suppressor 14-3-3s (Hodgson et al 2005).…”
Section: Transgenic Models Of Erbb2-induced Tumor Progressionmentioning
confidence: 99%